Analysis of Factors and Fraud Preventive Efforts in Company Financial Reports: A Literature Review Study - Putri, Mega Amalia; Oktaviani, Nurul; Sulistiya, Eulis; Muthmainnah, Sinta Shofiyatul (Asia Pacific Fraud Journal, 2024)
The research in this article aims to identify and provide an overview of the factors that cause fraud and explain efforts to prevent fraud in company financial reports. The results of the research show that there are seven factors that cause fraud in company financial reports, namely greed, opportunity, need, exposure, unshareable pressure/incentive, rationalization, and capacity. Apart from that, it turns out that digital technology has a negative impact in creating the potential to cause fraud in company financial reports. The preventive efforts that can be taken to prevent fraud in company financial reports are through improving risk management, internal control, and the use of digital forensic concepts which are expected to provide input for company management to avoid fraud in company financial reports from an early age. Apart from that, for future academics and researchers, it is hoped that this research can become a reference source for developing knowledge related to fraud.